In Search of Albion - Irwin C. Colin (London, Andre Deutsch, 2005)
Offering an anecdotal commentary on modern England, the author seeks out the traditional events, festivals and gigs. During his travels, he visits a succession of seriously bizarre events and rituals, and discovers that while the world shrinks, there`s an increasing tendency for communities to look inwardly at their own heritage.